2021
DOI: 10.3390/ijms22147254
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Sensitive Connexin Hemichannels in Neurons and Glia: Three Different Modes of Signalling?

Abstract: Connexins can assemble into either gap junctions (between two cells) or hemichannels (from one cell to the extracellular space) and mediate cell-to-cell signalling. A subset of connexins (Cx26, Cx30, Cx32) are directly sensitive to CO2 and fluctuations in the level within a physiological range affect their open probability, and thus, change cell conductance. These connexins are primarily found on astrocytes or oligodendrocytes, where increased CO2 leads to ATP release, which acts on P2X and P2Y receptors of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Therefore, our scRT-PCR results, together with those at the protein level (Leung et al, 2002) suggest that, at least for the subpopulation of DA neurons co-expressing the GABA phenotype, the connexin responsible for the electric coupling between DA neurons (Vandecasteele et al, 2005) could be Cx45. Furthermore, assuming that the expression of the mRNA for Cx26, Cx30, and Cx43 is translated into their respective proteins (Leung et al, 2002), the functional meaning of the expression of these connexins in pure DA neurons could be the forming of non-junctional hemichannels with the capability of releasing neurotransmitters or neuromodulators, like ATP or ADP (Goldberg et al, 1999;Hill et al, 2021), or even re-uptaking them, as in glial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our scRT-PCR results, together with those at the protein level (Leung et al, 2002) suggest that, at least for the subpopulation of DA neurons co-expressing the GABA phenotype, the connexin responsible for the electric coupling between DA neurons (Vandecasteele et al, 2005) could be Cx45. Furthermore, assuming that the expression of the mRNA for Cx26, Cx30, and Cx43 is translated into their respective proteins (Leung et al, 2002), the functional meaning of the expression of these connexins in pure DA neurons could be the forming of non-junctional hemichannels with the capability of releasing neurotransmitters or neuromodulators, like ATP or ADP (Goldberg et al, 1999;Hill et al, 2021), or even re-uptaking them, as in glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, heterologous electrical synapses has been found in the mouse retina between OFF bipolar cells and other retinal neurons (Hilgen et al, 2011); between fusiform GABAergic interneurons and spiny stellate excitatory cells in the somatosensory cortex (Venance et al, 2000); or between GABAergic neurons and principal (excitatory) neurons in the neocortex (Meyer et al, 2002). As for the expression of the other connexins (Cx26, Cx30, Cx31.1, Cx32, Cx43 ) in the other phenotypes, either they work as non-junctional connexons for the release of modulatory molecules (Goldberg et al, 1999;Hill et al, 2021), or work in unforeseen functions non related to channeling molecules, for instance, in the regulation of dendritic morphology and the development of synapses (Su et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 binds to a carbamylation motif in connexins Cx26, Cx30, and Cx32 and causes their hemichannels to open. Fluctuations in CO 2 levels within the tissue alter their open probability [ 59 ]. While it has been shown that direct CO 2 -gated Cx26 hemichannel opening and subsequent release of ATP mediate an important part of neurovascular coupling [ 47 ], the physiological significance of the CO 2 sensitivity of Cx30 and Cx32 has not yet been elucidated during exercise.…”
Section: Mechanisms Of Action Of Carbon Dioxide Therapymentioning
confidence: 99%